‘Silence is the sentence’: adult learners’ experiences of a co-created curriculum constructed through free writing tasks - Scott, Howard; Bennett, Pete; Hammond, Craig A (PRISM: Casting New Light on Learning, Theory and Practice, 2022)
This paper outlines the pedagogical approaches taken on a University Access course, teaching predominantly mature students on a 12-week ‘inclusion in education’ module. The methods aimed to validate and develop literacy and academic skills for students undertaking undergraduate courses. Practice on the programme of study, replicated over three years, is informed by transformative learning theories. We outline how our developing praxis situates students’ self-concepts in confronting past biographical experiences of education and empowers them to improved literacy and purpose. We further propose that such andragogical approaches to teaching and learning can potentially serve as a model for improved literacy practices in post-compulsory education in England – a curriculum and qualification regime in radical need of overhaul and replacement.